Genetically Modified Herbicide Resistant Rapeseed in Germany: A Socio-Economic Assessment - Philipp Wree; Johannes Sauer (German Journal of Agricultural Economics (GJAE), 2016)
The cultivation of transgenic rapeseeds is currently banned in Germany. Considering the reversibility, irreversibility and uncertainty in the context of costs and benefits of introducing herbicide-resistance rapeseeds (HR), we determine the maximum incremental social tolerable irreversible costs (MISTICs) of this technology for Germany. Results indicate that banning HR genetically modified
Keywords: 330